BUILDING CONSUMER ENGAGEMENT IN SOCIAL MEDIA: A SYSTEMATIC LITERATURE REVIEW (Journal of Business Management and Accounting, 2024)
This study aims to investigate the dimensions of customer engagement (CE) in social media and what theories and methods are employed to scrutinize CE on social media. This study systematically used the literature review of 77 articles. Through Scopus-indexed academic databases, this study found and assessed peer-reviewed journal papers focused on social media and consumer engagement from 2018 to 2022. In this study, the current issues and research gaps for designing and developing future research are presented as well. This research analyzed the dimensions, theories, variables, methods, social media types, and previous business and spatial contexts. Most researchers illustrated CE as giving likes, comments, and shares on social media. Sixteen theories of the prior research were employed to investigate consumer engagement. This study positively impacts social media and consumer engagement by suggesting new insight for analyzing the related literature. They include modifying the CE in social media, reflecting the interaction between brand and customer phenomena, using other theories that exclude sixteen approaches that have been identified, and applying different methods such as experimental or mixed methods. Therefore, a comprehensive explanation of the consumer engagement framework on social media can be explained holistically by further studies.